(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
This paper explores how research on visual journalism can apply visual methods to analyze journalistic coverages, considering characteristics that emerge in the contemporary context of convergence and platformization, such as labor precarization, image profusion in the digital environment, journalistic image production decentralization, and multiplatform circulation. We applied three methods in a case study to understand how Folha de S. Paulo portrayed the Brazilian presidential election campaign of 2022 in six months of publications on the outlet’s website: (1) image grids; (2) computer vision networks; and (3) timelines. We identified that the research on visual journalism can benefit from applying these methods as they align the quantitative and qualitative aspects of research. At the same time, analyzing images in groups allows for comparative observations of the images in relation to each other and the coverage as a whole.